Effect of Different Dosage Form of Saindhavadiyoga in the Management of Computer Vision Syndrome: A Pilot Study (AYUSHDHARA, 2022)
Eyes have a unique position among all the sense organs. Primary importance has been given for the protection of eyes by ancient Indian scholar because without eyes whole world is full of darkness. With the advancement of science development of many electronic gadgets like computer mobile etc, which has been produce new diseases. Among those diseases computer vision Syndrome is one of them. In modern system there is no permanent cure of CVS. In Ayurvedic text there is no description of Computer Vision Syndrome but it can be a Anukta vyadhi as describe by a Charak. Some of ocular symptoms of computer vision syndrome can be correlated with Sushkaksipaka as describe by Acharya sushrut and A.Hridya. Modern medicine do not have a definite treatment for this problem except lubricating eye drops whereas Ayurvedic kriyakalpas that is Ayurvedic local ocular therapies could suggest definite treatment to cure the computer vision syndrome along with the change in working style and correction of refractive error. Drugs which are describe in the treatment of Suskhakshipaka have potent property to reduce the clinical features of CVS. So in this clinical trial, I have used different dosage form of Saindhavadiyoga in the management of CVS. Study was conducted among the BHU computer professionals and all the patient were divide in the three group. In the group A eye drop and Anjana of Saindhavadi yoga was given, in the Group B only Carboxy Methyl Cellulose eye drop was given while in the group C only Tarpan therapy was given with Saindhavadighrita All the group have positive result results in reduction of signs and symptoms of CVS without any side effect which are produce by the preservative of Artificial tear drops. But in the group C have better results in comparison to other two group, it was occur due to oleation, nutritive antioxidant property of Ghrita and Yogvahi property of Ghrita which increase the bioavailbilty of drug along with other content of the drug.